Calling without calling: Barghouti, Derrida and 'the international day of telephones'. Issue 9 (2nd September 2022) - Jackson, Sarah
ABSTRACT: Drawing on research into telecommunications in the region by Helga Tawil-Souri (2013, 2015), this essay focuses on the literary, cultural and political implications of telephony in Israel-Palestine. Analysing the telephone in Mourid Barghouti's I Saw Ramallah (2000) and I Was Born There, I Was Born Here (2011), I argue that Barghouti's memoirs of exile are structured by an impossible logic where picking up the phone means not getting through. Demonstrating the ways that the lines of communication within and between communities are crossed, complicated, and often cut entirely, I point to the ways that the oppressive religious, political and geographical boundaries are not only mirrored but also significantly extended through the telecommunications infrastructure in the occupied territories. The essay reads Barghouti alongside Jacques Derrida's account of telephoning in Israel in 'Avowing – The Impossible' (1998). Suggesting new connecting lines between the texts, I examine how Israeli control of airspace, infrastructure, and cellular networks contribute to Eyal Weizman's (2007) model of the vertical architecture of the state – how, in effect, using the telephone for both Barghouti and Derrida recalls the Blanchotian syntagma of ' X sans X ': calling without calling.